1990
DOI: 10.1182/blood.v76.9.1807.1807
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characteristics of cerebrospinal fluid cells in children with acute lymphoblastic leukemia at diagnosis

Abstract: The presence of meningeal involvement in children with acute lymphoblastic leukemia (ALL) may have important prognostic and therapeutic implications. Conventional methods of diagnosing central nervous system (CNS) leukemia rely on the interpretation of cerebrospinal fluid (CSF) cell morphology, which may produce ambiguous results in the presence of minimal leukemic involvement. A methodology has been developed for immunophenotyping small numbers of CSF cells while preserving cell morphology. CSF samples from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thirty-six percent of CSF samples in that study were also examined for the simultaneous presence of nuclear terminal deoxynucleotidy1 transferase (TdT) and demonstrated higher numbers of positive cells for both TdT and CD10. The authors concluded that a large proportion of children with ALL and negative CSF cytology may have CNS disease consistent with the presence of occult leukemic involvement, which can be detected with CD10/TdT staining [ 22 ].…”
Section: Csf Biomarkers Reflecting Cns Disease In Pediatric Patienmentioning
confidence: 99%
“…Thirty-six percent of CSF samples in that study were also examined for the simultaneous presence of nuclear terminal deoxynucleotidy1 transferase (TdT) and demonstrated higher numbers of positive cells for both TdT and CD10. The authors concluded that a large proportion of children with ALL and negative CSF cytology may have CNS disease consistent with the presence of occult leukemic involvement, which can be detected with CD10/TdT staining [ 22 ].…”
Section: Csf Biomarkers Reflecting Cns Disease In Pediatric Patienmentioning
confidence: 99%
“…The finding that cytomorphologically suspicious cells are TdT-negative may exclude CNS leukemia; the finding of TdT positivity (in red blood cell-free samples!) is highly predictive of, but not decisive for, CNS involvement [60,63,64].…”
Section: Diagnosis/relapse ("Staging")mentioning
confidence: 99%
“…SCNSL, particularly of the leptomeninges, has been reported with an overall frequency of 3 . 7-9% in different series for extracerebral NHL (Herman et al, 1979;Johnson et al, 1984) and in a range from 1% to 15% of acute lymphoblastic leukaemia (ALL) in children at diagnosis (Homans et al, 1990).…”
mentioning
confidence: 99%
“…Transformed lymphocytes showing mitotic activity or atypical features may be seen in CSF samples in benign conditions and may contribute to false-positive results (Borowitz et al, 1980;Pearson et al, 1982). False negative cytologic results also remain a problem because of the small number of malignant cells which may be present in CSF samples, and in some instances multiple CSF examinations may be required to obtain a definitive diagnosis (Ersbøll et al, 1985;Homans et al, 1990). One objective method is to demonstrate monoclonality of a lymphoid population by surface markers using antibodies against immunoglobulin (Ig) heavy and light chains (Li et al, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation